Development of Blended Learning (Syncronous vs. Asyncronous) Physical Education Health and Recreation Models - Agusti Mardikaningsih; Praharisti Kurniasari (Madrosatuna: Journal of Islamic Elementary School, 2019)
One of the success learning process is appropriat learning design and in accordance with the conditions of learners and the learning environment. The purpose of designing a study is to improve and enhance the quality of learning. Based on the observations made by the researcher team teaching theoretical subjects in students found especially PJKR tendency kinesthetic learning pattern is a pattern of learning absorb information through physical practice. The purpose of this research is the development of a draft development know Learning Blended Learning Model (syncronous vs. Asynchronous) at the Teachers' Training College Budi Utomo. To learn more about whether blended learning (syncronous and asyncronous) appropriate for use in student sports that have these problems, it is essential that research efforts further to the researchers took the title of Model Development Learning Blended Learning (syncronous vs. Asynchronous) On Student Education Department of Sport Teachers' Training College Budi Utomo Malang. This development research using ADDIE Model. ADDIE Model is a model of the learning system of a general nature and is one of the models in the product development, application of the ADDIE model of instructional design facilitates the learning environment tailored to the existing problems. Each stage in the model ADDIE evaluations are available, so that each stage will affect the next stage. Based on trials that have been carried out to subject matter experts, media specialists and students can be concluded that the Development Model of Learning Blended Learning In Teachers' Training College Student Department of Sport Education Budi Utomo Malang have valid criteria / feasible. It is necessary for sustainability and cooperation in implementing the model.